2018
DOI: 10.5152/ejbh.2018.3853
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Patients with Synchronous Primary Breast and Thyroid Carcinoma

Abstract: Although synchronous presentation of breast and thyroid cancer is rare, surgical treatment of both of these tumors can be safely performed at the same time. Association of these tumors should be evaluated by large scaled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Although concurrent robotic ALND and laparoscopic cholecystectomy is not a preferred approach, doing so can reduce the need for repeated surgeries and anesthesia. In support thereof, previous studies have suggested that simultaneous co‐operations with mastectomy are feasible and safe 12‐15 . Nevertheless, further study is necessary to evaluate the safety and feasibility of cooperations, including mastectomy plus cholecystectomy or other types of surgery, in the near future.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although concurrent robotic ALND and laparoscopic cholecystectomy is not a preferred approach, doing so can reduce the need for repeated surgeries and anesthesia. In support thereof, previous studies have suggested that simultaneous co‐operations with mastectomy are feasible and safe 12‐15 . Nevertheless, further study is necessary to evaluate the safety and feasibility of cooperations, including mastectomy plus cholecystectomy or other types of surgery, in the near future.…”
Section: Discussionmentioning
confidence: 94%
“…In support thereof, previous studies have suggested that simultaneous co-operations with mastectomy are feasible and safe. [12][13][14][15] Nevertheless, further study is necessary to evaluate the safety and feasibility of cooperations, including mastectomy plus cholecystectomy or other types of surgery, in the near future.…”
Section: Pathology and Adjuvant Therapymentioning
confidence: 99%
“…The histology of the breast cancer that develops after thyroid cancer is different than the general population, with a greater percentage of ER/PR-positive tumors [ 19 ]. Although indicated by many studies, an association between breast and thyroid cancer still remains controversial [ 20 ]. The high percentage of male patients with ER/PR positive might lead to the conclusion that male breast cancer patients need a careful examination and evaluation of the thyroid, in order to exclude the thyroid malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients diagnosed with synchronous BC–TC can undergo simultaneous or sequential surgery [ 26 , 27 ]. In a series of 12 patients who were diagnosed preoperatively with synchronous BC–TC, they all underwent simultaneous mastectomy and thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The only postoperative complications were seroma and infection in two separate patients. All the patients were still disease-free at the end of their follow-up period of 15.6 months [ 27 ]. This shows that simultaneous thyroidectomy and mastectomy are quite safe and feasible.…”
Section: Discussionmentioning
confidence: 99%